Survey of Detection SIP Malformed Messages - Mourade Azrour; Mohammed Ouanan; Yousef Farhaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Session Initiation Protocol (SIP) is an application layer protocol designed to control and establish multimedia sessions over internet. SIP gaining more and more popularity as it is used by numerous applications such as telephony over IP(ToIP). SIP is a text based protocol built on the base of the HTTP and SMTP protocols. SIP suffers from certain security threats which need to be resolved in order to make it a more efficient signaling protocol. In this work, we review the proposed works aimed to detect SIP malformed messages that can cause security problem. Then, we classify the type of malformed SIP message and compare between the mechanisms used to reinforce the detection of malformed SIP message attack.